When Sophie thinks she can't... - Bang, Molly; Stern, Ann (Ann Swanson) (The Blue Sky Press, an imprint of Scholastic Inc., 2018)
Sophie is discouraged because she always struggles with math and puzzles--until her teacher shows her the hidden value of "try" and "yet."